An interlaboratory comparison to quantify oxidative potential measurement in aerosol particles: challenges and recommendations for harmonisation - P. A. Dominutti; J.-L. Jaffrezo; A. Marsal; T. Mhadhbi; R. Elazzouzi; C. Rak; F. Cavalli; J.-P. Putaud; A. Bougiatioti; N. Mihalopoulos; N. Mihalopoulos; D. Paraskevopoulou; et al. (Atmospheric Measurement Techniques)
This paper presents the findings from a collaborative interlaboratory comparison exercise designed to assess oxidative potential (OP) measurements conducted by 20 laboratories worldwide. This study represents an innovative effort as the first exercise specifically aimed at harmonising this type of OP assay, setting a new benchmark in the field.